Monetary policy, inflation and the level of economic activity in Brasil after the real plan: Stylized facts from SVAR models - Brisne J. V. Céspedes; Elcyon Caiado Rocha Lima; Alexis Maka (Institute for Applied Economic Research (ipea), 2015)
This article investigates the stochastic and dynamic relationship of a group of Brazilian macroeconomic variables (price and industrial production indexes, nominal exchange rate, short and medium-run nominal interest rates) for the period after the Real Plan (1996-2004). We adopt, as has become usual in the literature, several SVAR (structural VAR) models to uncover stylized facts for the short-run impacts of the identified exogenous sources of fluctuations of this selected set of variables. A distinctive feature of this article is the employment of Directed Acyclic Graphs (DAG) to obtain the contemporaneous causal order of the variables used to identify the SVAR models. Another distinguishing characteristic is the careful attention paid to monetary policy developments after the Real Plan when splitting our sample in two subsamples (1996/07-1998/08 and 1999/03-2004/12). The main results are: a) in response to a positive short run interest rate innovation, during the 1999-2004 subperiod, the output and the price level decrease - however, the output response is faster and the price level responds with a lag of near four months; b) for the 1996-1998 subperiod, the most likely effect of a positive short run interest rate innovation is the reduction of the price level (also with a four months lag), even though there is a large uncertainty in this response, and the reduction of output; c)short run interest rate innovations are one of the most important sources of temporary fluctuations in the level of economic activity for both subsamples; and d) exogenous shocks to the exchange rate and to the medium term interest rate are for the 1999-2004 period, the most important sources of inflation rate fluctuation.
Keywords: E31; C32; 330